2006
DOI: 10.1176/appi.ps.57.1.133
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in the Use of Second-Generation Antipsychotics for the Treatment of Schizophrenia

Abstract: In this sample, blacks were less likely than whites to receive second-generation antipsychotics, demonstrating a persistent gap in the quality of care for patients with schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 11 publications
(15 reference statements)
3
27
1
Order By: Relevance
“…Antipsychotic discontinuation is a significant predictor of relapse (Robinson et al 1999 Racial disparities in antipsychotic treatment have been reported in several studies (Bagchi et al 2004;dosReis et al 2002;Kilbourne and Pincus 2006;Kreyenbuhl et al 2003;Mallinger et al 2006). African-Americans are more likely to receive first generation antipsychotic medications relative to Whites or non-African-Americans (Bagchi et al 2004;Kilbourne and Pincus 2006;Mallinger et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antipsychotic discontinuation is a significant predictor of relapse (Robinson et al 1999 Racial disparities in antipsychotic treatment have been reported in several studies (Bagchi et al 2004;dosReis et al 2002;Kilbourne and Pincus 2006;Kreyenbuhl et al 2003;Mallinger et al 2006). African-Americans are more likely to receive first generation antipsychotic medications relative to Whites or non-African-Americans (Bagchi et al 2004;Kilbourne and Pincus 2006;Mallinger et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…African-Americans are more likely to receive first generation antipsychotic medications relative to Whites or non-African-Americans (Bagchi et al 2004;Kilbourne and Pincus 2006;Mallinger et al 2006). Moreover, African-Americans have a shorter duration of treatment and receive higher daily doses compared to Whites (dosReis et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Differences in treatment according to race have been noted in adult diseases such as breast cancer, coronary heart disease, hypertension and schizophrenia. [17][18][19][20] We postulated that differences in delivery patterns for breech presentation may also exist by race, thereby contributing to racial disparities in neonatal outcome.…”
Section: Introductionmentioning
confidence: 99%
“…A more recent study (Mallinger 2006) suggested that African American patients were six times less likely to receive an SGA and half as likely to receive clozapine as White people after controlling for clinical and sociodemographic factors. Possible reasons for this are prescribers' beliefs that African American patients may not adhere to clozapine treatment or to its blood monitoring requirement, or that clinicians are apprehensive about the efficacy of clozapine in Black and minority ethnic groups, which are poorly represented in clinical trials and report a higher prevalence of metabolic complications (Kelly 2006).…”
Section: Variability Of Clozapine Prescribing Among Different Ethnic mentioning
confidence: 99%